SURVEI TENTANG PROSES BELAJAR MENGAJAR DI SEKOLAH MENENGAH KEJURUAN DALAM RANGKA PELAKSANAAN TUJUH RUANG LINGKUP PENJASORKES DALAM KURIKULUM TINGKAT SATUAN PENDIDIKAN (STUDI PADA SMKN 8 SURABAYA) - ARISONA DWI PUTERA, RICKO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the School Based Curriculum, each school has discretion in formulating and implementing a school curriculum based on the needs and characteristics of the schools and their respective regions. Accordingly, this study tries to find out how the process of drafting and implementation of SBC in particular adjustment seven scope of physical education in SMK Negeri 8 Surabaya. Through qualitative research methods descriptive study describes the implementation of the seven scope of physical education . Then, through this study is expected to provide information for human education, especially focusing on physical education about SBC and adjustments of seven scope of physical education. In conclusion, in SMK Negeri 8 Surabaya in accordance with the guidelines of the National Education Standards Agency 2006 (BSNP), whereas adjustment of seven scope of physical education  done through meetings with the benchmark situation and the condition of school facilities and infrastructure which SMKN 8 Surabaya is a tourism group  vocational school and the needs of learners where the majority of learners are female. Overall percentage of the seven scope of physical education in SMK Negeri 8 Surabaya is the scope of sports and games is 17.56 %, the scope of physical development activities is 14.86 %, the scope of gymnastics activity is 16.21%, the scope of rhythmic activity is 16.21%, the scope of  aquatic activity is 14.86%, the scope of outdoor education is  6.75%, and the scope of health is 13.51%. Keywords : physical education, seven scope of physical education, School Based Curriculum